2005
DOI: 10.1348/096317904x22926
|View full text |Cite
|
Sign up to set email alerts
|

Test of a service profit chain model in the retail banking sector

Abstract: Research has shown that organizational subunits where employee perceptions are favourable enjoy superior business performance. The service profit chain model of business performance (Heskett, Sasser, & Schlesinger, 1997) has identified customer satisfaction as a critical intervening variable in this relationship. This paper examines the relationships between organizational climate, employee attitudes, customer satisfaction, and sales performance in the retail‐banking sector. The role of customer satisfaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 65 publications
(74 reference statements)
2
116
0
Order By: Relevance
“…Some empirical examinations of applying service profit chain to various businesses and industries are available. Gelade and Young (2005); Loveman (1998) both verified the links of service profit chain in retail banking, and found the result generally support the relationships of employee satisfaction and loyalty to customer satisfaction and loyalty to finally financial performance of a company. Another positive study of Brazil banks made by Kamakura, Mittal, de Rosa, and Mazzon (2002) proved that branch managers will obtain higher level of performance if they can manage to maintain high level of employee satisfaction.…”
Section: Introductionmentioning
confidence: 61%
“…Some empirical examinations of applying service profit chain to various businesses and industries are available. Gelade and Young (2005); Loveman (1998) both verified the links of service profit chain in retail banking, and found the result generally support the relationships of employee satisfaction and loyalty to customer satisfaction and loyalty to finally financial performance of a company. Another positive study of Brazil banks made by Kamakura, Mittal, de Rosa, and Mazzon (2002) proved that branch managers will obtain higher level of performance if they can manage to maintain high level of employee satisfaction.…”
Section: Introductionmentioning
confidence: 61%
“…Researchers like Armistead and Kiely, (2003); Gelade and Young, (2005);Homburg (2009);Yee, Yeung, and Cheng, (2011);Williams and Naumann, (2011);; Kanyurhi (2013) tested S-PC's links in different industries, at different locations and found close association among SPC's variables. Therefore, based on results and comparison of regression results (R 2 and ANOVA) of three tiers, it is found that the values of R 2 for the entire variables are positive and significant, which shows that the results are in line with assumptions.…”
Section: Comparing Regression Results (R2 and Anova) Of The Three Tiers'mentioning
confidence: 99%
“…Items have been operationalized based on previous studies and by adapting them to the private banking context. These studies include the works of Cronin and Taylor (1992), Meyer Goldstein (2003), Gelade and Ivery (2003) and Gelade and Young (2005). Furthermore, items from other studies were adapted according to the defined characteristics of the proposed dimension (Loveman, 1998;Silvestro & Cross, 2000).…”
Section: Methodology and Data Descriptionmentioning
confidence: 99%